From the 1931 sterling devaluation to the breakdown of Bretton Woods: Robert Triffin's analysis of international monetary crises - Ivo Maes; Ilaria Pasotti (National Bank of Belgium, 2023)
Robert Triffin (1911-1993) was one of the main protagonists in the international monetary debates in the postwar period. He became famous with his book Gold and the Dollar Crisis, published in 1960, in which he predicted the end of the Bretton Woods system. In his analysis there, Triffin was very much marked by the breakdown of the gold exchange standard in the early 1930s. In his view, the growth of foreign exchange reserves after World War Two repeated, but on a much larger scale, their similar expansion after the First World War. Triffin argued that the gold exchange standard had been a highly fragile construction as funds could move in and out due to changes in relative interest rates and/or changes in exchange rate expectations. The focus of this paper is on Triffin's analysis of the sterling devaluation of 1931 throughout his writings, from his early articles on the 1935 devaluation of the Belgian franc to his writings after the breakdown of the Bretton Woods system. The aim is twofold: to provide an assessment of Triffin's view of the interwar period and assess the significance of his analysis of the interwar period for his view on the Bretton Woods system.
Keywords: A11; B22; B31; E30; E50; F02; F32; 330; Robert Triffin; Bretton Woods system; gold exchange standard; pound sterling; Triffin dilemma